Social Networks, Personalized Advertising, and Privacy Controls - Tucker, Catherine E. (Journal of Marketing Research, 2014)
This article investigates how Internet users’ perceptions of control over their personal information affect how likely they are to click on online advertising on a social networking website. The analysis uses data from a randomized field experiment that examined the effectiveness of personalizing ad text with user-posted personal information relative to generic text. The website gave users more control over their personally identifiable information in the middle of the field test. However, the website did not change how advertisers used data to target and personalize ads. Before the policy change, personalized ads did not perform particularly well. However, after this enhancement of perceived control over privacy, users were nearly twice as likely to click on personalized ads. Ads that targeted but did not use personalized text remained unchanged in effectiveness. The increase in effectiveness was larger for ads that used more unique private information to personalize their message and for target groups that were more likely to use opt-out privacy settings.